Awkwafina is Nora from Queens. Season 1 [videorecording (DVD)]. - Awkwafina, 1988-; Wong, B. D.; Chinn, Lori Tan; Yang, Bowen (Comedy Partners, 2020)
"Awkwafina stars as Nora, an unemployed 27-year-old living with her dad and her grandma in Queens, New York, as she attempts to inch toward adulthood and out of the shadow of her tech wunderkind cousin, Edmund."--Container